Clinical experience with combination BRAF/MEK inhibitors for melanoma with brain metastases: a real-life multicenter study. Issue 1 (February 2019) - Drago, Joshua Z.; Lawrence, Donald; Livingstone, Elisabeth; Zimmer, Lisa; Chen, Tianqi; Giobbie-Hurder, Anita; Amann, Valerie C.; Mangana, Joanna; Siano, Marco; Zippelius, Alfred; Dummer, Reinhard; Goldinger, Simone M.; et al.
Abstract : BRAF and MEK kinase inhibitors can be highly effective in treating BRAF -mutant melanomas, but their safety and activity in patients with active/symptomatic brain metastases are unclear. We sought to shed light on this open clinical question. We conducted a multicenter retrospective study on real-life patients with melanoma and active brain metastases treated with combination BRAF/MEK inhibitors. A total of 65 patients were included (38 men and 27 women; median age: 49 years). Of them, 53 patients received dabrafenib/trametinib, 10 received vemurafenib/cobimetinib, one received encorafenib/binimetinib, and one received vemurafenib/trametinib. We did not observe any unexpected treatment-related safety signals in our cohort. Overall, 17 patients continued on therapy through the cutoff date. After initiation of therapy, steroid dose could be decreased in 22 of 33 patients (11 tapered off entirely), anticonvulsants were stopped in four of 21, and narcotics were stopped in four of 12. Median progression-free survival from the start of therapy was 5.3 months (95% confidence interval: 3.6–6.1), and median overall survival was 9.5 months (95% confidence interval: 7.7–13.5). A total of 20 patients were surviving at the cutoff date. Univariate analysis of age, sex, ulceration status, thickness, stage, location, or lactate dehydrogenase did not reveal significant predictors of progression-free survival or overall survival within our cohort, but multivariate analysis suggested that older age, lower risk location of original lesion, and nodular melanoma are poor prognostic indicators. Combination therapy with BRAF/MEK inhibitors is a viable treatment option for patients with BRAF -mutant melanoma and brain metastases, but further studies should help to define the optimal treatment approach in this population.